Physicochemical characterization of a navy bean (Phaseolus vulgaris) protein fraction produced using a solvent-free method. (1st October 2016) - Jafari, Mousa; Rajabzadeh, Amin Reza; Tabtabaei, Solmaz; Marsolais, Frédéric; Legge, Raymond L.
Highlights: Electrostatic separation used to produce protein- and starch-rich fractions from navy bean flour. Properties of the protein-rich fraction compared to isolates from a conventional wet process. Protein distribution of the protein-rich fraction similar to that of the feed flour. Native protein structure conserved with electrostatic separation. Abstract: A solvent-free electrostatic separation method was employed to separate navy bean flour (NBF) into protein-rich (PR) and starch-rich (SR) fractions. The physicochemical properties of NBF and separated fractions were compared to proteins (navy bean isolate (NBI) and 7S globulin) prepared using a wet process. Gel electrophoresis confirmed that the protein distribution in the isolated fractions was similar to that of NBF. The protein profile of NBI and 7S globulin was found to be devoid of certain proteins that were found in the NBF and PR fraction. Amino acid analysis revealed that the NBI and 7S globulin had a lower content of sulfur-containing amino acids compared to NBF and the electrostatically isolated fractions. CD and fluorescence spectroscopy confirmed that denaturation of the proteins during the acid precipitation is likely. This novel solvent-free electrostatic separation process preserves the native protein structure found in NBF and improves the recovery of some of the smaller MW proteins.